1992
DOI: 10.1093/infdis/166.5.985
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Interaction of Interferon-  and Interferon-  in Coxsackievirus B3-Infected Carrier Cultures of Human Myocardial Fibroblasts

Abstract: The antiviral effects of human interferon-beta (IFN-beta) and human recombinant interferon-gamma (rIFN-gamma) were studied in persistently coxsackievirus B3-infected carrier cultures of human myocardial fibroblasts over a period of 21 days. Synergism was observed with concentrations as low as 30 IU of IFN-beta plus 10 IU of rIFN-gamma/mL, reducing mean viral titers from 6.0 x 10(7) to 1.3 x 10(4) pfu/mL and number of infected cells from 14.4% to 0.1% as determined by quantitative in situ hybridization. Higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 0 publications
4
40
0
1
Order By: Relevance
“…Stability of the cell membrane could also be another important factor in the ability of infected cells to survive infection, without lysis. In previous studies, the distinct susceptibility of different cell types to long-term infection has been related to the production of IFNs (15,35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stability of the cell membrane could also be another important factor in the ability of infected cells to survive infection, without lysis. In previous studies, the distinct susceptibility of different cell types to long-term infection has been related to the production of IFNs (15,35).…”
Section: Discussionmentioning
confidence: 99%
“…However, it cannot be excluded that TNF-␣ produced by infected cells may synergize with the other cytokines in enhancing expression of adhesion proteins, extravasation of leukocytes, and differentiation and proliferation of lymphocytes (25,32,41). Cytokineblocking experiments only partially reduced expression of adhesion molecules, indicating that besides IL-6 and IL-8, other molecules, such as IFNs (15,35) or IL-1 (42), may contribute to the up-regulation of ICAM-1 and VCAM-1 (41).…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial cells themselves may serve as antigen-presenting cells Savinov et al, 2003). The infection was also accompanied by increased production of IFN-, that has a role in initiation and maintenance of chronic CVB infection, as shown for other infected cell lines including islet  cells, and in line with the extensive studies documenting abnormal localization of IFN- in the pancreas of type 1 diabetic patients , Huber et al, 1990, Conaldi et al, 1997Heim et al, 1992). As stated above, IFN- may be responsible for a viral expansion of non-specific T cell responses, including autoreactive T cells.…”
Section: Coxsackievirus Infection and Endothelial Cellsmentioning
confidence: 78%
“…Stability of the cell membrane could also be another important factor in the ability of infected cells to survive infection, without lysis. In previous studies, the distinct susceptibility of different cell types to long-term infection has been related to the production of interferons (Conaldi et al, 1997;Heim et al, 1992). It has also been suggested that the persistent infection of cultured HUVEC may be due to down-regulation of viral receptors in infected cells.…”
Section: Coxsackievirus Infection and Endothelial Cellsmentioning
confidence: 98%
“…Type II interferon (IFN␥) signaling is initiated by the paracrine action of natural killer cells, which become activated upon CVB3 infection (44). Cotreatment of cells with IFN␤ and IFN␥ synergistically inhibits CVB3 replication (104), and IFN␤ treatment alone has shown some success in clearing persistent CVB3 infections (98). Phosphatases are rare among interferon-stimulated genes (105), but some viruses directly perturb interferon action by upregulating phosphatase activity (106).…”
Section: Fig 6 Egf Stimulates Subcellular Erk Phosphorylation and Ementioning
confidence: 99%